Biodiesel (methyl oleate) synthesis in the presence of pyridinium and aminotriazolium acidic ionic liquids: Kinetic, thermodynamic studies. (1st January 2022) - Tankov, Ivaylo; Mustafa, Zilya; Nikolova, Radoslava; Veli, Anife; Yankova, Rumyana
Graphical abstract: Highlights: Biodiesel synthesis using pyridinium and aminotrizolium ionic liquids is studied. Catalytic activity (ATN < PN < PHS) depends on the acidic scale (Hammett function). 10 wt% PHS, of 55 °C and M = 7.0 are optimal conditions for biodiesel synthesis. Biodiesel yield passes through a maximum at reactants molar ratio within 7.0–10.0. The thermodynamic parameters Δ H r °, Δ S r °, Δ G r °, Δ H ≠, Δ S ≠ and Δ G ≠ are determined. Abstract: Kinetics and thermodynamics of biodiesel (methyl oleate) synthesis using the protic ionic liquids pyridinium hydrogen sulfate (PHS), pyridinium nitrate (PN) and 4-amino-1 H -1, 2, 4-triazolium nitrate (ATN) as catalysts are studied in the current work for the first time. Rate of the biodiesel production is directly related to acidity of the ionic liquids used and their internal hydrogen bonding extent. A detailed thermodynamic analysis on the title reaction is conducted as well. To optimize the reaction conditions, influence of the reaction temperature (25–55 °C), initial alcohol-to-acid molar ratio (1.0–15.0) and catalyst loading (5–15 wt% with respect to the substrate mass) is investigated in details. Catalyst reusability is evaluated for five cycles. Based on the experimental data, a plausible mechanism of biodiesel synthesis is offered. Catalytic performance of the PHS sample in the biodiesel synthesis is remarkably higher than that of the nitrate anion-based ionic liquids. Reaction temperature of 55 °C, an initial reactants molar ratio of 7.0 and a catalyst loading of 10 wt% are established as optimal conditions for the process of biodiesel production. Values of 43.09 kJ/mol and 91.29 × 10 5 l/mol × min are calculated as activation energy and pre-exponential factor, respectively. Δ S r ° and Δ H r ° for the process of biodiesel synthesis are found to be 42.32 J/mol × K and 9.64 kJ/mol, respectively. Moreover, Δ H ≠ (40.49 kJ/mol) and Δ S ≠ (−162.31 J/mol × K) are established as well. The respective Δ G r ° (−4.241 kJ/mol) and Δ G ≠ (93.727 kJ/mol) at reaction temperature of 55 °C are obtained.